Legal Protection in Specified-Term Employment Contracts: Striking a Balance between Workers' Rights and Obligations - Dahris Siregar (Istinbath : Jurnal Hukum, 2025)
Specified-term employment contracts (PKWT) have been a common practice in modern employment schemes. However, this practice poses challenges in fulfilling the workers’ normative rights. This study evaluates the effectiveness of legal protection for workers bound by PKWT within the framework of Indonesian labor law, particularly following the enactment of the Job Creation Law. Using a legal-normative approach and analyzing regulations, court rulings, and labor law literature, this study maps the structural vulnerabilities faced by contract workers. The research findings indicate that PKWT is often inconsistently applied to permanent jobs, extended beyond the time limit, and sometimes includes unilateral clauses in contracts, which are detrimental to workers. Outsourcing practices further worsen workers' bargaining position, especially when combined with ill-defined PKWT schemes that create quasi-permanent employment status. Many workers face legal uncertainty, lack of social security, and no access to severance pay or maternity protection. Labor inspections have proven unreliable in preventing systemic violations, due to limited enforcement resources and overlapping regulations. On the other hand, the application of market flexibility logic that dominates the Job Creation Law actually weakens the principle of industrial relations justice. Therefore, a redesign of the PKWT legal protection system is essential to ensure it is more responsive to workers' structural vulnerabilities and to guarantee clarity in norms, effective oversight mechanisms, and collective protection through labor unions.